2017
DOI: 10.1016/j.soilbio.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of tropical forest conversion to oil palm on soil bacterial community and network structure

Abstract: Tropical forest conversion to agriculture is a major global change process. Understanding of the ecological consequences of this conversion are limited by poor knowledge of how soil microorganisms respond. We analyzed the response of soil bacteria to conversion from primary rain forest to oil palm plantation and regenerating logged forest in Malaysia. Bacterial diversity increased by approximately 20% with conversion to oil palm because of higher pH due to liming by plantation managers. Phylogenetic clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 74 publications
(93 reference statements)
2
23
0
Order By: Relevance
“…In our present study, co-occurrence networks in melt ponds and periglacial rivers suggested that most of the involved nodes belonged to the rare sub-communities. This pattern has previously been reported from other glacial environments in Tibet Plateau [23] and from other habitats, such as soil [58,59], rivers [60], and oceans [61]. Moreover, the over-proportional roles of rare taxa were also shown by our finding that all 7 keystones in melt ponds and 11 out of 12 keystones in periglacial rivers were affiliated with rare OTUs.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiesupporting
confidence: 90%
See 1 more Smart Citation
“…In our present study, co-occurrence networks in melt ponds and periglacial rivers suggested that most of the involved nodes belonged to the rare sub-communities. This pattern has previously been reported from other glacial environments in Tibet Plateau [23] and from other habitats, such as soil [58,59], rivers [60], and oceans [61]. Moreover, the over-proportional roles of rare taxa were also shown by our finding that all 7 keystones in melt ponds and 11 out of 12 keystones in periglacial rivers were affiliated with rare OTUs.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiesupporting
confidence: 90%
“…Based on the increasing nutrient resource from melt ponds to periglacial rivers, a niche difference is expected, which allows the bacterial communities to adapt quickly to available nutrients without the need to establish interactions with neighboring microorganisms [68]. As a consequence, the higher connectivity of bacterial communities in melt ponds would result in greater vulnerability to disturbance because the whole community will be more affected by the other nodes [58]. In contrast, we found that the network in melt ponds had significantly shorter average path length than did that of the periglacial rivers.…”
Section: Higher Competitive and Connected Network Of Bacterial Communmentioning
confidence: 99%
“…Changes in transitivity, average harmonic geodesic distances and geodesic efficiencies also support the above scenario. Lower transitivity indicates weaker interactions and couplings within the community 52 , hence stronger stability of the co-occurrence network is achieved 53 . The smaller average harmonic geodesic distances and the larger geodesic efficiencies of the Control network indicate that all nodes are closer 54 , 55 and fertilization decreases the interspecies collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation of land cover and land use change plays a crucial role in management natural resources as well as in academic research. In deforestation, the development of models is accomplished by several useful factors [24], [25], [26]: Providing a better understanding of how deforestation factors play a role Production of a future scenario for deforestation Forecast of forest destruction In order to support the design of responsible forestry policy The purpose of this study is to develop a simple spatial model that can predict deforestation using artificial neural networks [27], [28], [29].…”
Section: Introductionmentioning
confidence: 99%